Effects of Curcumin on The Changes in Some Acute Phase Proteins in Aflatoxin B1 Applied Rats - Ercan Keskin; Deniz Uluışık; Durmuş Hatipoğlu (Türk Spor ve Egzersiz Dergisi)
This research was carried out to evaluate the possible effects of curcumin on acute phase proteins in aflatoxin applied rats. In the study, 38 healthy male Wistar Albino rats were used. Group I animals was no applied. Animals in Group II were orally given 1 ml 10% DMSO daily for 60 days. Animals in Group III were orally given 300 mg/kg curcumin dissolved in 10% DMSO daily for 60 days. Animals in Group IV were orally given 250 µg/kg aflatoxin B1 dissolved in 10% DMSO daily for 60 days. Animals in Group V was orally given 250 µg/kg aflatoxin B1 dissolved in 10% DMSO and 300 mg/kg curcumin dissolved in 10% DMSO daily for 60 days. At the end of the study, nitric oxide, amyloid-A, haptoglobin and ceruloplasmin were determined in blood samples taken from all animals. In this study, nitric oxide, amyloid-A, haptoglobin and ceruloplasmin levels with aflatoxin B1 administration were found to be significantly higher than the control group (p lt;0.05). In the group in which aflatoxin and curcumin were administered together, nitric oxide, amyloid-A, haptoglobin and ceruloplasmin levels were lower than in the aflatoxin group (p lt;0.05). In conclusion, the obtained data indicated that administration of curcumin may be useful to alleviate the abnormalities in acute phase proteins resulting from aflatoxicosis.